Inventory of forestry products in Nigeria : National Bureau of Statistics (NBS). - Nigeria (Abuja, Nigeria : National Bureau of Statistics, 2007)
The compilation consist of all categories of plants. It provides inventory information on identification of the forest products by their English, local and botanical/zoological names in various states and local government areas. Further analyses on distribution by zones were also made to derive the national summary.
Ferdera Republic of Nigeria, September 2007
Produced under the auspices of the Ferderal Government Economic Reform & Governnce Projecg [ERGP].
oif 12/02/2020
Ref.
Keywords: Forests and forestry; Nigeria